Biomedical applications of polyphosphazenes - Ogueri, Kenneth S. (Med Devices Sens, 2020)
Ever since the pioneering research efforts on their utility in biomedicine, polyphosphazene polymers have witnessed enormous growth and expansion in several biomedical applications due to their unique properties. The development of this exceptional biodegradable system with extraordinary design flexibility, property tunability and neutral bioactivity could stimulate an unprecedented paradigm in biomaterial design. Thus, polyphosphazenes are, undoubtedly, the next-generation biomaterials. This editorial provides a brief perspective on the promising prospects of polyphosphazene-based biomaterials for medical device technology, focusing mainly on the authors’ work on this particular polymeric system.